2020
DOI: 10.5194/egusphere-egu2020-18295
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The November 11 2019 Le Teil, France M5 earthquake: a triggered event in nuclear country

Abstract: <p>An earthquake of magnitude 5 (Mw 4.9) occurred near the town of Le Teil, France on November 11 2019, causing damage locally and concern due to its proximity to nuclear facilities. Despite its moderate magnitude, this earthquake offers unique opportunities to advance basic and applied research on earthquakes in general, including our understanding of the largest and most destructive earthquakes and induced seismicity. We present here an overview of the source characteristics of this event and, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 0 publications
2
18
0
Order By: Relevance
“…Such low values raise the question of the tectonic loading of faults, however the occurrence of the Le Teil earthquake (2019/11/11, M L 5.4, no. 1 on Figure 9) led Delouis et al [2019] and Ampuero et al [2020] to conclude that, although the earthquake was probably triggered by quarry activity since the 19th century (considered as an external forcing), the magnitude reached requires a prior and significant tectonic loading. The tectonic loading of the La Rouvière fault, source of the Le Teil earthquake, at a very weak strain rate is also supported by field evidences of its Holocene-Late Pleistocene tectonic activity [Ritz et al, 2021].…”
Section: Tectonic and Non-tectonic Earthquakes In Se Francementioning
confidence: 99%
See 1 more Smart Citation
“…Such low values raise the question of the tectonic loading of faults, however the occurrence of the Le Teil earthquake (2019/11/11, M L 5.4, no. 1 on Figure 9) led Delouis et al [2019] and Ampuero et al [2020] to conclude that, although the earthquake was probably triggered by quarry activity since the 19th century (considered as an external forcing), the magnitude reached requires a prior and significant tectonic loading. The tectonic loading of the La Rouvière fault, source of the Le Teil earthquake, at a very weak strain rate is also supported by field evidences of its Holocene-Late Pleistocene tectonic activity [Ritz et al, 2021].…”
Section: Tectonic and Non-tectonic Earthquakes In Se Francementioning
confidence: 99%
“…A triggered earthquake occurs on a tectonically loaded fault and the additional stress related to an external forcing triggers this earthquake which would nevertheless have occurred anyway in the future. As previously mentioned, the large excavation of limestone in a quarry located on the hanging wall of the La Rouvière fault (LRF on Figure 20) is certainly the triggering cause of the Le Teil earthquake [Delouis et al, 2019, Ampuero et al, 2020]. An induced earthquake can occur on a fault that is not tectonically loaded and, in this case, such an earthquake would probably never have occurred in the absence of the external forcing.…”
Section: Tectonic and Non-tectonic Earthquakes In Se Francementioning
confidence: 99%
“…The shallow location may be related to quarry extraction directly above the rupture area (ref. [10][11][12] ). In a few cases, small to moderate-sized anthropogenic earthquakes with reverse-faulting style are reported in the immediate proximity of quarries (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary seismological analysis indicate a reverse-faulting focal mechanism (FM) along a NE-SW trending fault located within the northeastern termination of the Cévennes Faults system between the Massif Central and the Southeastern basin, with a focal depth between 1 and 3 km (https://www.emsc-csem.org/ Earthquake/earthquake.php?id=804595#map). This shallow hypocenter and its proximity to a large limestone quarry raised the question of the possible relationship between the mass of rock extracted and the triggering of the earthquake 3 . This also suggested that the rupture could have reached the surface, which is uncommon for both such a magnitude and for the region.…”
mentioning
confidence: 99%